Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's systematically break down and solve the given equation step-by-step.
Given equation:
[tex]\[ \log_2(x) \cdot \log_x\left(\frac{\log_{|x|} \sqrt[9]{3}}{\log_{\sqrt{3}} |x|}\right) = -1 \][/tex]
First, recognize the logarithmic expressions and simplify them using properties of logarithms.
1. Simplify [tex]\(\log_{|x|} \sqrt[9]{3}\)[/tex]:
[tex]\[ \log_{|x|} \sqrt[9]{3} = \log_{|x|}(3^{1/9}) \][/tex]
Using the logarithmic property [tex]\(\log_b(a^c) = c \log_b(a)\)[/tex], we can write:
[tex]\[ \log_{|x|} (3^{1/9}) = \frac{1}{9} \log_{|x|} (3) \][/tex]
2. Simplify [tex]\(\log_{\sqrt{3}} |x|\)[/tex]:
[tex]\[ \log_{\sqrt{3}} |x| = \frac{\log |x|}{\log \sqrt{3}} \][/tex]
Since [tex]\(\sqrt{3} = 3^{1/2}\)[/tex], we can write:
[tex]\[ \log_{\sqrt{3}} |x| = \frac{\log |x|}{\frac{1}{2} \log 3} = \frac{2 \log |x|}{\log 3} \][/tex]
3. Combine these results into the given equation:
Substitute the simplified results into the equation:
[tex]\[ \log_2(x) \cdot \log_x\left(\frac{\frac{1}{9} \log_{|x|} (3)}{\frac{2 \log |x|}{\log 3}}\right) = -1 \][/tex]
Simplify the fraction inside the logarithm:
[tex]\[ \frac{\frac{1}{9} \log_{|x|} (3)}{\frac{2 \log |x|}{\log 3}} = \frac{\log_{|x|} (3)}{18 \log |x| / \log 3} = \frac{(\log 3) / (\log |x|)}{18 \log |x| / \log 3} = \frac{\log 3}{18 \log |x|} \][/tex]
Thus,
[tex]\[ \log_2(x) \cdot \log_x\left(\frac{\log 3}{18 \log |x|}\right) = -1 \][/tex]
4. Simplifying the logarithm inside further:
Use the property [tex]\(\log_x(a/b) = \log_x(a) - \log_x(b)\)[/tex]:
[tex]\[ \log_2(x) \cdot \left(\log_x(\log 3) - \log_x(18 \log |x|)\right) = -1 \][/tex]
5. Expanding [tex]\(\log_x(18 \log |x|)\)[/tex]:
[tex]\[ \log_x(18 \log |x|) = \log_x(18) + \log_x(\log |x|) = \frac{\log 18}{\log x} + \log_x(\log |x|) \][/tex]
Combine terms:
\[
\log_2(x) \cdot \left(\frac{\log (\log 3) -\left(\log 18 + \log (\log |x|)\right) }{\log(x)}\right) = -1
= -\frac{\log (\log 3) -\left(\log 18 + \log (\log |x|)\right )}{\log(x)} = \frac{1}{x^2}
}
We can expect \(\boxed{{3}
Given equation:
[tex]\[ \log_2(x) \cdot \log_x\left(\frac{\log_{|x|} \sqrt[9]{3}}{\log_{\sqrt{3}} |x|}\right) = -1 \][/tex]
First, recognize the logarithmic expressions and simplify them using properties of logarithms.
1. Simplify [tex]\(\log_{|x|} \sqrt[9]{3}\)[/tex]:
[tex]\[ \log_{|x|} \sqrt[9]{3} = \log_{|x|}(3^{1/9}) \][/tex]
Using the logarithmic property [tex]\(\log_b(a^c) = c \log_b(a)\)[/tex], we can write:
[tex]\[ \log_{|x|} (3^{1/9}) = \frac{1}{9} \log_{|x|} (3) \][/tex]
2. Simplify [tex]\(\log_{\sqrt{3}} |x|\)[/tex]:
[tex]\[ \log_{\sqrt{3}} |x| = \frac{\log |x|}{\log \sqrt{3}} \][/tex]
Since [tex]\(\sqrt{3} = 3^{1/2}\)[/tex], we can write:
[tex]\[ \log_{\sqrt{3}} |x| = \frac{\log |x|}{\frac{1}{2} \log 3} = \frac{2 \log |x|}{\log 3} \][/tex]
3. Combine these results into the given equation:
Substitute the simplified results into the equation:
[tex]\[ \log_2(x) \cdot \log_x\left(\frac{\frac{1}{9} \log_{|x|} (3)}{\frac{2 \log |x|}{\log 3}}\right) = -1 \][/tex]
Simplify the fraction inside the logarithm:
[tex]\[ \frac{\frac{1}{9} \log_{|x|} (3)}{\frac{2 \log |x|}{\log 3}} = \frac{\log_{|x|} (3)}{18 \log |x| / \log 3} = \frac{(\log 3) / (\log |x|)}{18 \log |x| / \log 3} = \frac{\log 3}{18 \log |x|} \][/tex]
Thus,
[tex]\[ \log_2(x) \cdot \log_x\left(\frac{\log 3}{18 \log |x|}\right) = -1 \][/tex]
4. Simplifying the logarithm inside further:
Use the property [tex]\(\log_x(a/b) = \log_x(a) - \log_x(b)\)[/tex]:
[tex]\[ \log_2(x) \cdot \left(\log_x(\log 3) - \log_x(18 \log |x|)\right) = -1 \][/tex]
5. Expanding [tex]\(\log_x(18 \log |x|)\)[/tex]:
[tex]\[ \log_x(18 \log |x|) = \log_x(18) + \log_x(\log |x|) = \frac{\log 18}{\log x} + \log_x(\log |x|) \][/tex]
Combine terms:
\[
\log_2(x) \cdot \left(\frac{\log (\log 3) -\left(\log 18 + \log (\log |x|)\right) }{\log(x)}\right) = -1
= -\frac{\log (\log 3) -\left(\log 18 + \log (\log |x|)\right )}{\log(x)} = \frac{1}{x^2}
}
We can expect \(\boxed{{3}
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.